PERBANDINGAN DIRI GENERASI Z TERHADAP KONSUMSI KONTEN MEDIA SOSIAL PLATFORM TIKTOK DALAM MEMBANGUN CITRA DIRI (SELF IMAGE) (STUDI PADA MAHASISWA UNIVERSITAS TEKNOLOGI SUMBAWA) - Febrina Safitri, Anggia; Hidayat, Ofi (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
TikTok has become a significant part of digital life, particularly among the younger generation. The platform influences how individuals perceive themselves and others through content consumption and social comparison. This study aims to further analyze how UTS students engage in self-comparison when consuming TikTok content in shaping their self-image. A qualitative approach was employed, using in-depth interviews with active TikTok users. The findings indicate that most UTS students, representing Generation Z, demonstrate strong evaluative abilities, especially in accurately assessing opinions and skills. Although TikTok content has the potential to influence perceptions of social values and self-image, the participants were able to remain critical and selective. Positive perceptions were more dominant, with content often seen as a source of inspiration and motivation. Participants also exhibited healthy patterns of social comparison, including upward comparison as a source of motivation, downward comparison as a means of reflection and gratitude, and comparison with similar individuals to form a realistic and positive self-image. Thus, content consumption and social comparison on TikTok serve as mechanisms of self-evaluation that support the development of a healthy self-image in the digital media era.